Pre-Columbian art from Central America and Colombia at Dumbarton Oaks - McEwan, Colin 1951-2020; Hoopes, John W. (Dumbarton Oaks Research Library and Collection, 2021)
"Catalogue of the collection of Pre-Columbian Art from Central America and Colombia at Dumbarton Oaks. The catalogue, written by leading international scholars of Pre-Columbian art history and archaeology, contains detailed analyses of specific works of art along with thematic essays situating these works within the broader context of greater Central American culture".
Keywords: Dumbarton Oaks Research Library and Collection; Sammlung; Präkolumbische Zeit; Kunst; Kolumbien; Zentralamerika; Dumbarton Oaks / Catalogs; Robert Woods Bliss Collection of Pre-Columbian Art / Catalogs; Indian art / Central America / Catalogs; Indian art / Colombia / Catalogs; Indians of Central America / Antiquities / Catalogs; Indians of South America / Colombia / Antiquities / Catalogs; Dumbarton Oaks; Robert Woods Bliss Collection of Pre-Columbian Art; Indian art; Indians of Central America / Antiquities; Indians of South America / Antiquities; Central America; Colombia; Catalogs; Katalog